Polyurethane material formed in water and preparation method thereof
By compounding polyols and optimizing catalysts, underwater molding polyurethane materials are prepared, which solves the leakage problem of polyurethane materials in underwater environments, achieves high strength, water resistance and good bonding properties, and is suitable for the waterproofing needs of underwater projects.
Patent Information
- Application Number
- CN202511042239.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-09-26
AI Technical Summary
Existing polyurethane materials are prone to softening after gelling in underwater environments, reducing strength and elastic modulus, powdering and falling off, and poor sealing, making it difficult to effectively solve the leakage problem of underwater projects. Traditional foaming agents have an impact on the ozone layer, and the process is complicated or has poor hydrolysis resistance.
A water-molded polyurethane material is prepared by using a compound combination of polyether polyol, polyester polyol, and polycarbonate diol, optimizing the molecular chain structure and cross-linking density, using an early rapid viscosity-increasing catalyst and an amine hydrate foaming agent, simplifying the preparation process and improving the hydrophobicity and cross-linking density of the material.
The prepared polyurethane material has excellent water resistance and mechanical properties underwater, high compressive and flexural strength, density greater than the foaming density in the air, good bonding performance, suitable for the waterproofing needs of underwater projects, and has no pollution to the environment.
Smart Images

Figure CN120699224A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane materials, and particularly relates to an underwater molding polyurethane material and a preparation method thereof. Background Art
[0002] Against the backdrop of large-scale national infrastructure development, an increasing number of dams, tunnels, subways, and other projects are entering large-scale construction and operation both domestically and internationally. The hydrogeological conditions encountered during construction are becoming increasingly complex, and various engineering hydrogeological disasters are a frequent occurrence. Furthermore, water leakage is common during the operational period of dams, buildings, and other underground structures. Grouting can improve the mechanical properties and overall stability of the ground, achieving water blocking, anti-seepage, and reinforcement. Grouting reinforcement has minimal impact on surrounding structures and groundwater levels, is cost-effective, minimally disturbs the in-situ soil, is simple to construct, is environmentally friendly and durable, and simultaneously blocks water and reinforces the foundation, making it a common method for treating groundwater leakage.
[0003] Traditional cement grouts have low injectability, long setting times, and low retention rates after dynamic water erosion, making it difficult to achieve ideal grouting results. While cement-water glass grouts can quickly block water, they also have poor injectability, making penetration grouting difficult, which in turn affects grouting effectiveness. Furthermore, cement-water glass grouts have poor water corrosion resistance and durability, impacting the overall quality and long-term stability of the project.
[0004] Polyurethane grouting technology perfectly solves these problems. Compared with traditional cement grouting maintenance and repair technology, two-component foamed polyurethane grouting materials have the characteristics of low viscosity, fast reaction speed, rapid strength improvement, good durability and no pollution to the environment. They are suitable for anti-leakage and foundation reinforcement grouting. However, current polyurethane materials mainly use water as a foaming agent, which often reacts violently when exposed to water, which is relatively inconsistent with their application in underwater environments. In underwater environments, the material is prone to softening after gelation, reduced strength and elastic modulus, powdering and falling, and poor sealing, making it difficult to fundamentally solve the leakage problem of underwater projects. Therefore, how to achieve leakage repair of polyurethane materials in underwater environments has become a challenging problem.
[0005] Patent CN106496503B invented a water-insensitive polyurethane grouting material and its preparation method by mixing polyol-modified xylene methane diisocyanate and polymethylene polyphenyl isocyanate in component A, using water and cyclopentane foaming agents. However, the density and strength retention rates of the polyurethane grouting material in water are still lower than 1.0, indicating that the material still undergoes partial reaction in water. In addition, the cyclopentane foaming agent has an impact on the ozone layer and is a product that must be eliminated and is not suitable for long-term use.
[0006] Patent CN117757025A utilizes hyperbranched polyester polyols and catechol-modified hyperbranched polyols to invent a water-insensitive polyurethane grouting material, preparation method, and use method. This method requires hyperbranching and modifying the polyester polyol, which is a relatively complex process. Polyester has high mechanical strength but poor hydrolysis resistance, which conflicts with long-term underwater application. Furthermore, the density and strength retention rates in underwater environments are not given, and its water sensitivity effect is unclear. Therefore, it is necessary to provide a two-component polyurethane material with a fast reaction speed, good fluidity, high bonding properties, light weight, high strength, durability, self-expansion, insensitivity to environmental water, and stable underwater performance, so as to overcome the defects of existing common polyurethane materials, realize the application of polyurethane materials in underwater water-sealed environments, and improve the load-bearing capacity and durability of polyurethane materials in water-rich and humid environments. Summary of the Invention
[0007] In view of the defects and problems of low density and strength retention in water of current water-insensitive polyurethane materials, the present invention provides an underwater molding polyurethane material and a preparation method thereof.
[0008] A water-molded polyurethane material, comprising component A and component B,
[0009] The component A is isocyanate;
[0010] The component B comprises the following raw materials in parts by weight:
[0011]
[0012]
[0013] The mass ratio of component A to component B is 1:(1.1-1.2).
[0014] In the above-mentioned water-molded polyurethane material, the isocyanate is polymethylene polyphenyl isocyanate, and the isocyanate index is 1.0-1.15.
[0015] In the above-mentioned water-molded polyurethane material, the polyol is a mixture of two or more of polyether polyol, polyester polyol and polycarbonate diol; the average functionality of the polyol is 2-5 and the molecular weight is 200-1000.
[0016] In the above-mentioned water-molded polyurethane material, the polyol is a mixture of polyether polyol, polyester polyol and polycarbonate diol, wherein the addition amount of polyether polyol is 30-40 parts, the addition amount of polyester polyol is 15 parts, and the addition amount of polycarbonate diol is 15 parts.
[0017] In the above-mentioned water-molded polyurethane material, the added amount of the polyether polyol is 35 parts.
[0018] In the above-mentioned water-molded polyurethane material, the foaming agent is an alcoholamine hydrate.
[0019] The above-mentioned water-molded polyurethane material, the catalyst includes a foaming catalyst and a viscosity-increasing catalyst, wherein the foaming catalyst is one or both of tertiary amine and morpholine catalysts; the viscosity-increasing catalyst is one or more of organic tin, bismuth or other rare earth organic metal catalysts.
[0020] In the above-mentioned water-molded polyurethane material, the chain extender is one or both of 1,4-butanediol and dipropylene glycol; and the cross-linking agent is trimethylolpropane.
[0021] In the above-mentioned water-molded polyurethane material, the foam stabilizer is an organic silicone oil stabilizer; the coupling agent is a silane coupling agent; and the plasticizer is an ester plasticizer.
[0022] The above-mentioned water-forming polyurethane material is prepared by adding the raw materials in component B into a container according to the ratio, heating to 55-65°C and stirring at high speed for 30-40 minutes to obtain component B; then quickly mixing component A and component B according to a set mass ratio, and quickly pouring the slurry into water that completely covers the slurry, and foaming to obtain the water-forming polyurethane material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention adopts a composite combination of polyether polyol, polyester polyol and polycarbonate. Through the synergistic effect of these three polyols, the soft segment structure of the polyurethane molecular chain is optimized, the hydrophobicity and cross-linking density of the material are enhanced, thereby reducing the penetration and damage of water molecules to the material structure; at the same time, a catalyst that rapidly increases viscosity in the early stage is used to accelerate the cross-linking reaction of the polyurethane material in the early stage of curing, quickly form a high-viscosity slurry, and prevent the water reaction caused by the diffusion of external water molecules inside the material; and an alcohol amine hydrate with weakly bound water is used as a foaming agent, which can reduce the connectivity between the free water in the material as a foaming agent and the water in the external environment, reduce the reaction between the external free water and the isocyanate in the material, and is conducive to the underwater grouting and molding of the polyurethane.
[0025] 2. The present invention adopts compound polyols to change the molecular structure and cross-linking degree of the material. By rationally selecting and proportioning different types of polyols, the cross-linking degree of the material can be adjusted, thereby affecting its mechanical properties. Polycarbonate diol is added on the basis of polyether polyol and polyester polyol. The high polarity and rigidity of the carbonate group of polycarbonate diol and its stronger molecular chain regularity can promote tighter molecular stacking, enhance the interaction force between polyurethane molecules, form a more stable cross-linking network, significantly improve the molding density in water, and at the same time improve the flexibility of the polyurethane material, thereby improving its compressive and flexural strength.
[0026] 3. The present invention simply physically mixes the raw materials according to a determined formula without the need for chemical reaction, resulting in a simple preparation process. Through the physical and chemical synergistic effect between the raw materials, a polyurethane material with excellent water insensitivity can be prepared in one step. In addition, the present invention preferably prepares the polyurethane material from various raw materials so that the foaming density in water is greater than the free foaming density in air, indicating that the water-molded polyurethane material prepared by the present invention has excellent water resistance, providing a new material solution for the waterproofing needs of underwater engineering, marine engineering, underground engineering and other fields.
[0027] 4. The polyurethane material prepared by the present invention foams evenly and densely in a water environment, has good toughness and strength, and the molding density in water is 415.8kg / m 3 (corresponding to the molding density in air is 332kg / m 3 ), has excellent mechanical properties, and its compressive and flexural strengths are 14.82MPa and 10.43Mpa respectively; and the mechanical properties of the polyurethane material prepared by the present invention are less affected by temperature, and the compressive and flexural strengths and apparent density of the material are good at 20°C; the anti-seepage performance of the material is improved with the increase of density, and the density reaches 592kg / m 3 When the amount of polyurethane material increases, its initial water seepage pressure reaches 1.06MPa; as the amount of polyurethane material increases, its bonding strength with steel gradually increases, and can reach a maximum of about 1.756MPa; and the material has good environmental corrosion resistance and will not affect the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a technical flow chart for preparing the water-molded polyurethane material of the present invention.
[0029] Figure 2 This is a polyurethane material sample prepared according to the present invention.
[0030] Figure 3 This is a morphology diagram of the pores of the polyurethane material prepared in the present invention.
[0031] Figure 4 This is the pore size distribution diagram of the polyurethane material prepared in the present invention.
[0032] Figure 5 This is a graph showing the change in water seepage pressure versus density of the polyurethane material prepared in the present invention. DETAILED DESCRIPTION
[0033] To address the shortcomings and problems of current water-insensitive polyurethane materials, such as low density and strength retention in water, the present invention has developed a two-component polyurethane material that exhibits rapid reaction speed, excellent fluidity, high adhesion, lightweight, high strength, durability, self-expansion, insensitivity to ambient water, and stable underwater performance. This overcomes the shortcomings of existing conventional polyurethane materials, enables the application of polyurethane materials in underwater sealed water environments, and improves the load-bearing capacity and durability of polyurethane materials in water-rich and humid environments. The present invention is further described below with reference to the accompanying drawings and specific examples.
[0034] The main raw materials used in the present invention are shown in Table 1 below.
[0035] Table 1 Main experimental raw materials
[0036]
[0037]
[0038] Examples 1-6: Component B and component A were mixed at a mass ratio of 1:1.2, wherein component A was polymethylene polyphenyl isocyanate with an isocyanate index R=1.05; the composition and proportion of component B in each example are shown in Table 2 below. The preparation method is to add the raw materials in component B according to the proportion into a container, heat to 55-65°C, and stir at high speed for 30-40 minutes to obtain component B; then, quickly mix component A and component B according to the set mass ratio, and quickly pour the slurry into water that completely covers the slurry, and foam to obtain the water-based polyurethane material.
[0039] Table 2 Distribution ratio and material properties of Group B in Examples 1-6
[0040]
[0041]
[0042] The viscosity-increasing catalyst D1 used in the above embodiment is a homemade mixture of stannous octoate (T-9) and organic bismuth (E20) in a ratio of 1:1; the plasticizer H1 used is a homemade mixture of diethylene glycol dibenzoate and citrate in a ratio of 1:1.2.
[0043] Examples 7-11: Component B and component A were mixed in a mass ratio of 1:1.2, wherein component A was polymethylene polyphenyl isocyanate with an isocyanate index of R=1.05; the component composition and proportion of component B in each example are shown in Table 3 below; the preparation method was the same as that in Example 1.
[0044] Table 3 Component ratios and material properties of Examples 7-11
[0045]
[0046] Examples 12-16: Component B and component A were mixed in a mass ratio of 1:1.2, wherein component A was polymethylene polyphenyl isocyanate with an isocyanate index of R=1.05; the composition and proportion of component B in each example are shown in Table 4 below; the preparation method was the same as that in Example 1.
[0047] Table 4 Component ratios and material properties of Examples 12-16
[0048]
[0049] Based on the results of the above examples, it can be seen from Table 2 that as the amount of polycarbonate diol added increases from 0 to 25 parts, the water molding density increases from 394.8 kg / m 3 Increased to 427.3kg / m 3 , showing an overall upward trend; this is mainly due to the high polarity and rigidity of the carbonate group of polycarbonate diol. Compared with polyether / polyester polyols, its molecular chain is more regular, which promotes tighter molecular stacking, thereby improving the overall density of the material.
[0050] In terms of mechanical properties, as the amount of polycarbonate diol added increases, the compressive strength increases from 13.69 MPa to 14.82 MPa, then slightly decreases to 14.29 MPa; the flexural strength increases from 9.71 MPa to 10.43 MPa, then decreases to 10.12 MPa. This is mainly because the addition of polycarbonate diol enhances the intermolecular interactions of the polyurethane material, forming a more stable cross-linked network, while improving the flexibility of the polyurethane material, thereby increasing its compressive and flexural strength. However, when the addition amount is too high, the polycarbonate diol will cause agglomeration or phase separation in the polyurethane matrix, which in turn destroys the original continuous phase structure of the polyurethane material, reduces the uniformity of the cross-linked network, and forms stress concentration points, resulting in a slight decrease in compressive and flexural strength.
[0051] In terms of water absorption, the rate of water absorption shows a continuous downward trend with increasing polycarbonate diol addition, dropping from 1.0711% to 0.5132%. This is primarily due to the carbonate groups in polycarbonate diol having lower affinity for water molecules than the ether bonds in polyether polyols and the ester bonds in polyester polyols, which reduces the overall polarity of the material and inhibits water adsorption. Furthermore, the addition of polycarbonate diol promotes the formation of a denser cross-linked structure, reducing the pores and channels within the material, thereby reducing water permeability.
[0052] As can be seen from Tables 3 and 4, when the total amount of polyether polyol and polyester polyol remains unchanged, as the polyester polyol content continues to increase, the density and water absorption of the water-molded polyurethane material show an overall upward trend. This is mainly because the polyurethane polymer molecular chain formed by the polyester polyol contains polar groups such as ester groups and amino groups, which causes the water absorption of the material to gradually increase, but the overall water absorption is less than 3%. Adjusting the amount of foaming agent, cross-linking agent, and chain extender has a significant impact on the performance of the polyurethane material. At the same time, combined with Table 2, it can be seen that the performance of the polyurethane material obtained by compounding polyether polyol, polyester polyol, and polycarbonate diol is relatively good, and the material performance is relatively excellent when the amount of polyether polyol is 35 parts, the amount of polyester polyol is 15 parts, and the amount of polycarbonate diol is 15 parts.
[0053] Comparative Example 1: This comparative example provides an underwater moldable polyurethane material. The difference is that the polyol in component B is a polyether polyol. Specifically, component B includes 65 parts of polyether polyol, 0.3 parts of triethylenediamine, 0.4 parts of viscosity-increasing catalyst D1, 0.5 parts of amine hydrate, 4 parts of trimethylolpropane, 8 parts of 1,4-butanediol, 1.5 parts of foam stabilizer 7705, 2 parts of silane coupling agent KH-550, and 15 parts of plasticizer ATBC. The preparation method is the same as that of Example 1.
[0054] The water foaming density of the prepared polyurethane material is 102.4 kg / m 3 The foaming density in air is 203.6kg / m 3 ; The compressive strength is 5.96MPa and the flexural strength is 2.74Mpa.
[0055] Comparative Example 2: This comparative example provides a water-molded polyurethane material, except that the specific components and contents of component B are different. Specifically, component B includes 35 parts of polyether polyol, 15 parts of polyester polyol, 15 parts of polycarbonate diol, 0.4 parts of triethylenediamine, 0.5 parts of water, 4 parts of trimethylolpropane, 8 parts of 1,4-butanediol, 1.5 parts of foam stabilizer 7705, 2 parts of silane coupling agent KH-550, and 15 parts of plasticizer DOTP. The preparation method is the same as that of Example 1.
[0056] The water foaming density of the prepared polyurethane material is 145.9 kg / m 3 The foaming density in air is 230.6kg / m 3 ; The compressive strength is 6.61MPa and the flexural strength is 3.93Mpa.
[0057] Comparative Example 3: This comparative example provides an underwater moldable polyurethane material, differing in the specific components and amounts of component B. Specifically, component B includes 35 parts of polyether polyol, 15 parts of polyester polyol, 15 parts of polycarbonate diol, 0.7 parts of triethylenediamine, 0.5 parts of amine hydrate, 4 parts of trimethylolpropane, 8 parts of 1,4-butanediol, 1.5 parts of foam stabilizer 7705, 2 parts of silane coupling agent KH-550, and 15 parts of plasticizer ATBC. The preparation method is the same as that of Example 1.
[0058] The water foaming density of the prepared polyurethane material is 197.9 kg / m 3 The foaming density in air is 245.8kg / m 3 ; The compressive strength is 7.32MPa and the flexural strength is 5.76Mpa.
[0059] Comparative Example 4: This comparative example provides an underwater moldable polyurethane material, differing in the specific components and amounts of component B. Specifically, component B includes 35 parts of polyether polyol, 15 parts of polyester polyol, 15 parts of polycarbonate diol, 0.7 parts of triethylenediamine, 0.4 parts of viscosity-increasing catalyst D1, 0.5 parts of amine hydrate, 4 parts of trimethylolpropane, 8 parts of 1,4-butanediol, 1.5 parts of foam stabilizer 7705, 2 parts of silane coupling agent KH-550, and 15 parts of plasticizer ATBC. The preparation method is the same as that of Example 1.
[0060] The water foaming density of the prepared polyurethane material is 377.5 kg / m 3 The foaming density in air is 333.7kg / m 3 ; The compressive strength is 9.52MPa and the flexural strength is 7.61Mpa.
[0061] Test Example 1: Anti-permeability test
[0062] This test example refers to the permeability evaluation method of hydraulic concrete, adopts the sample size and test instrument in the anti-permeability grade method, prepares samples with the formula of Example 4, measures the initial water seepage pressure of samples with different densities, and draws a curve of the relationship between specimen density and initial water seepage pressure to evaluate the anti-permeability performance of polyurethane waterproofing materials.
[0063] Referring to my country's concrete impermeability grade test standards, a homemade specimen mold was used to produce polyurethane specimens of varying densities by controlling the grouting volume. The specimens were truncated cone-shaped, with specific dimensions of 175mm in diameter at the top, 185mm in diameter at the bottom, and 150mm in height.
[0064] Test steps:
[0065] (1) Wipe the specimen clean and let it dry. Then evenly put 3-5 full-circle sealing rings on the side of the composite frustum specimen, and then press the specimen into the anti-seepage main membrane using a digital hydraulic press;
[0066] (2) Start the concrete water permeability tester, open the valves under the six test positions, and let water seep out from the five holes to fill the test pit. Close the tester and install the sealed test piece on the tester;
[0067] (3) Increase the water pressure of the anti-permeability tester directly to 0.2 MPa, and slowly press water into the deformation joint of the composite frustum specimen. When the water pressure no longer increases, close the valve. At this time, the air in the deformation joint will be discharged along with the water. Repeat the above steps until the air in the joint is completely discharged.
[0068] (4) Start the water pressure of the water-resistance tester from 0.1 MPa, and then increase the water pressure by 0.1 MPa every 8 hours until water seeps from the upper end face of the specimen. Stop the test and record the water pressure.
[0069] By controlling the grouting volume, polyurethane specimens with different densities were produced. A total of 6 specimens with different densities were tested for their anti-permeability properties. The results are shown in Table 5 below.
[0070] Table 5 Water seepage pressure values of water-insensitive polyurethane materials with different densities
[0071]
[0072] The relationship between water seepage pressure and density is as follows: Figure 4 shown.
[0073] From Table 5 and Figure 4 It can be seen that the anti-seepage performance of the water-molded polyurethane material of the present invention increases with the increase of the material density. When the material density reaches 390kg / m 3 When the initial water seepage pressure reaches 0.77Mpa, according to the hydraulic concrete anti-seepage grade classification method, the anti-seepage grade is equivalent to grade 7. When the material density reaches 592kg / m 3 When the initial water seepage pressure reaches 1.06MPa, it can withstand a water head of 100 meters, which is equivalent to a concrete anti-seepage grade of 10. When conducting anti-seepage grouting for underground projects, the grouting volume can be controlled and the density of the polyurethane waterproofing material can be adjusted according to the actual needs of different projects to meet the anti-seepage requirements of different projects.
[0074] Test Example 2: Adhesion Performance Test
[0075] This test used the pull-off method to test the adhesive properties of the water-insensitive polyurethane material prepared in Example 4. The adhesion between the water-insensitive polyurethane material and steel was determined. In this test, the steel and the water-insensitive polyurethane material were first foamed and then coagulated together. The steel and water-insensitive polyurethane were then stretched using an electronic tensile testing machine, and the maximum adhesion between the two was measured at breakage.
[0076] Test steps:
[0077] (1) Debug the electronic tensile testing machine and install the fixture for testing tensile performance on the testing machine;
[0078] (2) Fix the prepared bonding sample on the fixture, adjust the tensile speed of the instrument to 5 mm / s, turn on the switch, and start the measurement;
[0079] (3) During the test, when you hear the sound of a break in the bond between the steel and the water-insensitive polyurethane material, write down the reading on the test machine display;
[0080] (4) Replace other samples and continue measuring until all samples have been measured;
[0081] (5) Arrange the sheared specimens, number them, and place them in the specimen cabinet; at the same time, turn off the power of the testing machine and arrange the tensile fixture.
[0082] The bond strength of the sample was calculated from the measured bond force. The final bond strength value was obtained by dividing the bond force by the bond area of the sample. The results are shown in Table 6 below.
[0083] Table 6 Adhesion test results of water-molded polyurethane materials
[0084]
[0085] Table 6 shows that the bond strength of the specimens increases with increasing polyurethane content, before slightly decreasing at a certain level. This is because an appropriate amount of polyurethane can fill tiny gaps on the surface of the materials and form a good bond, thereby improving bond strength. However, using too much polyurethane may result in an excessively thick bond layer, which in turn leads to a certain decrease in bond strength.
[0086] Test Example 3: Burial Test
[0087] This test case illustrates the durability of water-insensitive polyurethane grouting materials through an on-site burial test. That is, a batch of material specimens are buried underground. After 3 months, 6 months, 9 months, and 1 year, a group of specimens are taken out to test their mass loss and changes in compressive strength, and to observe whether there is any biological erosion.
[0088] (1) Specimen shape and size
[0089] The shape of the test piece is cylindrical: 30 mm in diameter and 60 mm in height.
[0090] (2) Number of test pieces
[0091] A batch of test specimens with basically the same density were made and divided into 5 groups, 3 in each group, for a total of 15 test specimens.
[0092] (3) Test method
[0093] One day after the specimens were formed, their initial density and compressive strength were tested. The remaining specimens were all buried in the soil outdoors at a depth of 1.5m. After waiting for 3 months, 6 months, 9 months, and 1 year, the mass and compressive strength of the specimens were tested at room temperature, and the average value was taken as the test result.
[0094] (4) Test results
[0095] Due to the limitation of research time, this experiment only tested the data of specimens after being buried in the soil for 3 months, 6 months, 9 months and 1 year, as shown in Table 7.
[0096] Table 7 Outdoor deep buried specimens
[0097]
[0098] Careful examination of the water-insensitive polyurethane grouting material specimens after 3 months, 6 months, 9 months and 1 year of burial found that although the specimens had faded slightly, their structure had not changed and there was no mold or rot.
[0099] After testing and evaluating the density and compressive strength of the specimens, it was found that the density of the water-insensitive polyurethane grouting material specimens remained essentially unchanged after being buried for 3, 6, 9, and 1 month, and the compressive strength remained essentially unchanged at later stages, indicating that the material's long-term performance is stable in a buried environment. Furthermore, test data showed that compared to the initial molding stage (1 day old), the compressive strength showed a significant increase over time, indicating that as the early molding time increases, the cross-linking polymerization reaction of the material continues, and only after a certain period of time does this reaction completely end, and the material's performance tends to stabilize.
[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A polyurethane material formed in water, characterized in that: Including component A and component B, The component A is isocyanate; The component B comprises the following raw materials in parts by weight: 65~67 parts of polyol 0.4~0.9 parts of catalyst 4~5 parts of cross-linking agent Chain extender 6~10 parts 1~1.5 parts of foam stabilizer 2 parts coupling agent 0.5~1.5 parts of foaming agent Plasticizer 14.2~18.2 parts; The mass ratio of component A to component B is 1:(1.1-1.2).
2. The underwater forming polyurethane material according to claim 1, characterized in that: The isocyanate is polymethylene polyphenyl isocyanate, and the isocyanate index is 1.0-1.
15.
3. The underwater forming polyurethane material according to claim 1, characterized in that: The polyol is a mixture of two or more of polyether polyol, polyester polyol and polycarbonate diol; the average functionality of the polyol is 2-5 and the molecular weight is 200-1000.
4. The underwater forming polyurethane material according to claim 3, characterized in that: The polyol is a mixture of polyether polyol, polyester polyol and polycarbonate diol, wherein the addition amount of polyether polyol is 30-40 parts, the addition amount of polyester polyol is 15 parts, and the addition amount of polycarbonate diol is 15 parts.
5. The underwater forming polyurethane material according to claim 4, characterized in that: The added amount of the polyether polyol is 35 parts.
6. The underwater forming polyurethane material according to claim 1, characterized in that: The foaming agent is an alcoholamine hydrate.
7. The underwater forming polyurethane material according to claim 1, characterized in that: The catalyst includes a foaming catalyst and a viscosity-increasing catalyst, wherein the foaming catalyst is one or both of tertiary amine and morpholine catalysts; the viscosity-increasing catalyst is one or more of organic tin, bismuth or other rare earth organic metal catalysts.
8. The underwater forming polyurethane material according to claim 1, characterized in that: The chain extender is one or both of 1,4-butanediol and dipropylene glycol; and the cross-linking agent is trimethylolpropane.
9. The underwater forming polyurethane material according to claim 1, characterized in that: The foam stabilizer is an organic silicone oil stabilizer; the coupling agent is a silane coupling agent; and the plasticizer is an ester plasticizer.
10. The underwater forming polyurethane material according to claim 1, characterized in that: The preparation method is to put the raw materials of component B into a container according to the proportion, heat it to 55-65°C and stir it at high speed for 30-40 minutes to obtain component B; then quickly mix component A and component B according to the set mass ratio, and quickly pour the slurry into water that completely covers the slurry, and foam it to obtain the water-molded polyurethane material.
Citation Information
Patent Citations
Water-insensitive polyurethane grouting material and its preparation method
CN106496503B